2002
DOI: 10.1063/1.1455692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MgO and Sc2O3 passivation on AlGaN/GaN high-electron-mobility transistors

Abstract: Unpassivated AlGaN/GaN high-electron-mobility transistors show significant gate lag effects due to the presence of surface states in the region between the gate and drain contact. Low-temperature (100 °C) layers of MgO or Sc2O3 deposited by plasma-assisted molecular-beam epitaxy are shown to effectively mitigate the collapse in drain current through passivation of the surface traps. These dielectrics may have advantages over the more conventional SiNX passivation in terms of long-term device stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 27 publications
0
98
0
Order By: Relevance
“…On the other The current collapse effects have often been observed GaN/AlGaN SG HFETs under quiescent gate stress 19 or pulse-mode gate stress. 17,18,24,37 The collapse is also induced by drain stress. 1,18,37 The mechanism for the current collapse is not clarified yet.…”
Section: Application Of the Al 2 O 3 -Based Passivation Structure mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other The current collapse effects have often been observed GaN/AlGaN SG HFETs under quiescent gate stress 19 or pulse-mode gate stress. 17,18,24,37 The collapse is also induced by drain stress. 1,18,37 The mechanism for the current collapse is not clarified yet.…”
Section: Application Of the Al 2 O 3 -Based Passivation Structure mentioning
confidence: 99%
“…Inoue and co-workers 23 fabricated the IG AlGaN/GaN HFET using native oxide of AlGaN itself formed by thermal oxidation at 900°C. Luo et al 24 reported the passivation effects of the MBE-grown MgO films on the AlGaN/GaN HFETs.…”
Section: Introductionmentioning
confidence: 99%
“…9 The current collapse effects have often been observed AlGaN/GaN HFETs under quiescent gate stress 10 or pulsemode gate stress. 11,12 The collapse is also induced by drain stress. 13,14 Hasegawa and coworkers 5 explained that the charging effects of the surface electronic states, consisting of a U-shaped surface state continuum and V N -related nearsurface deep donor, play a dominant role for the current collapse, 5 as schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Scandium oxide has attractive band gap and thermal lattice properties for use on GaN. 5 A Sc 2 O 3 layer was shown to effectively mitigate the collapse in drain current through passivation of the surface traps. 5,6 Additionally, it was demonstrated that Sc 2 O 3 can be used simultaneously as a gate oxide and as a surface passivation layer for AlGaN/GaN high electron mobility transistors.…”
Section: Introductionmentioning
confidence: 99%
“…5 A Sc 2 O 3 layer was shown to effectively mitigate the collapse in drain current through passivation of the surface traps. 5,6 Additionally, it was demonstrated that Sc 2 O 3 can be used simultaneously as a gate oxide and as a surface passivation layer for AlGaN/GaN high electron mobility transistors. 7 However, the gate oxide material must satisfy several criteria: in addition to the electronic function of a gate dielectric, the gate oxide material must maintain a high dielectric constant, and serve as a diffusion barrier against diffusion of material from the top electrode.…”
Section: Introductionmentioning
confidence: 99%